Clinical and Laparoscopic Findings in Infertile Couples with a Normal Hysterosalpingogram - Mehmet Ali Serkan Özkul; Gülnur Özakşit; Rana Karayalçın; Sarp Özcan; Mustafa Uğur (Medical Network, 2009)
OBJECTIVE: The aim of this study was to evaluate retrospectively the clinical course of infertile couples with a normal hysterosalpingogram (HSG) to assess the diagnostic value of subsequent laparoscopy (L/S). STUDY DESIGN : Retrospective evaluation of laparoscopic findings of 527 patients after a normal hysterosalpingogram. RESULTS : The infertile couples (N: 527) were aged 27±5,0 SD years, with 4,3±2.8 years of infertility. All patients were required laparoscopy because of failure to conceive or suspected pelvic pathology based on symptoms or the results of a pelvic examination. Among the 527 patients receiving L/S, pelvic pathology was found in 314 (59.6% ). Corrective surgery performed in 37 (7.2%) patients. CONCLUSION: In our study we conclude that clinical risk factors were not predict laparoscopically proven abnormalities. In some pathologies encountered during laparoscopy we do not generally perform corrective surgery. In surgically corrected cases monthly fecunditiy rates were not as high as normal fertile women. It is still unclear to declare to performe laparoscopy in order to detect, correct and enhance fertility after a normal HSG.